Rhino 5 advanced techniques - McCulloch, Rob; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2012)
"In this advanced Rhino 5 training course, author Rob McCulloch dives deeper into the application of the tools available to you in this 3D modeling software. This tutorial is taught at an intermediate to advanced level, and it is recommended that you are familiar and comfortable with the basics of Rhino 5, or have previously completed the Infinite Skills Learning Rhino 5 training course.This majority of this tutorial is presented in a project-based fashion. You will work on designs from start to finish, learning new tools and new ways to apply them as you go along. You will create models of a computer mouse, desk lamp, car hood and hood scoop, a ring, a power drill, and more. As you progress through the video training, more and more advanced topics are introduced in each project, increasing your skills with the Rhino 5 toolset. By the time you have completed this computer based training course on Rhino 5, you will be able to create advanced 3D models using the application of expert techniques for your designs. Extensive working files are included to allow you to work on the same files that the author uses throughout the training course."--Resource description page.
Title from resource description page (viewed January 7, 2015)
Date of publication taken from resource description page.
Presenter, Rob McCulloch.
Keywords: Three-dimensional modeling; Computer-aided design; Electronic books